2014
DOI: 10.1902/jop.2014.130595
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Porphyromonas gingivalis to Corroded Commercially Pure Titanium and Titanium‐Aluminum‐Vanadium Alloy

Abstract: A higher degree of corrosion on the titanium surface may promote increased bacterial attachment by oral pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 46 publications
(99 reference statements)
1
29
1
4
Order By: Relevance
“…This may be related to the bacterial surface properties and sensitivity to Al or V components in the alloy. Barão et al (2014), observed higher attachment of Porphyromonas gingivalis to cp-Ti than Ti6Al4V. They suggest that the reduced attachment of P. gingivalis on Ti6Al4V could be explained by the antimicrobial effect of vanadium, as reported by Tousley, Wren, Towler, and Mellott (2012).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This may be related to the bacterial surface properties and sensitivity to Al or V components in the alloy. Barão et al (2014), observed higher attachment of Porphyromonas gingivalis to cp-Ti than Ti6Al4V. They suggest that the reduced attachment of P. gingivalis on Ti6Al4V could be explained by the antimicrobial effect of vanadium, as reported by Tousley, Wren, Towler, and Mellott (2012).…”
Section: Discussionmentioning
confidence: 70%
“…This may be related to the bacterial surface properties and sensitivity to Al or V components in the alloy. Barão et al (), observed higher attachment of Porphyromonas gingivalis to cp‐Ti than Ti6Al4V. They suggest that the reduced attachment of P .…”
Section: Discussionmentioning
confidence: 96%
“…Irrespective of the etiologic factor for initiation of titanium corrosion, the resulting corroded surfaces of dental implants may offer amenable niches for colonization by bacteria. Porphyromonas gingivalis has shown increased attachment to corroded titanium disks compared with non‐corroded titanium disks, indicating that a corroded surface may promote increased bacterial colonization 13 . In addition, lipopolysaccharides from Gram‐negative bacterial cell walls have demonstrated a high affinity to titanium, while also promoting dissolution of the TiO 2 layer in pH 4.0 to 7.0 which is found in the oral environment 7 .…”
mentioning
confidence: 99%
“…Once set, the cylinder pairs were incubated in a water bath at 37 C for 7 days. The cemented cylinders for each test cement (n=12) were subjected to a shear bond test, with the testing setup reported in a previous study, 16 and the peak shear force was recorded. The debonded surfaces of the Ti alloy disks were examined under a light microscope (BX51 TRF; Olympus Corp) at ×10 magnification to record and compare the mode of failure.…”
Section: Methodsmentioning
confidence: 99%
“…Color change has been associated with corrosion of the titanium alloy, 14 which may account for the higher than expected bond strength values. Although this may be of benefit mechanically, 15 the corrosion effects have been linked to implant failure 16 and an increase in pathogenic microbial adherence to the alloy. 17 Also, fluorinated acidic dental cements increase titanium corrosion susceptibility.…”
mentioning
confidence: 99%